2009
DOI: 10.1074/jbc.m109.001669
|View full text |Cite
|
Sign up to set email alerts
|

Slc26a9 Is Inhibited by the R-region of the Cystic Fibrosis Transmembrane Conductance Regulator via the STAS Domain

Abstract: SLC26 proteins function as anion exchangers, channels, and sensors. Previous cellular studies have shown that Slc26a3 and Slc26a6 interact with the R-region of the cystic fibrosis transmembrane conductance regulator (CFTR), (R)CFTR, via theSlc26 genes and proteins have attracted the attention of physiologists and geneticists. Why? Slc26a1 (Sat-1) was characterized as a Na ϩ -independent SO 4 2Ϫ transporter (1). Given the transport characteristics of the founding member of the gene family, Slc26 proteins were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 66 publications
5
77
0
Order By: Relevance
“…Co-expression studies in HEK cells showed that CFTR expression led to a marked increase in Cl Ϫ /OH Ϫ and Cl Ϫ /HCO 3 Ϫ exchange mediated by SLC26A3, -A4, and -A6 (48). It is also possible that, under resting conditions, association between CFTR and pendrin blocks AE activity, a phenomenon recently described for Slc26a9 and the regulatory domain of CFTR in Xenopus oocyte co-expression studies (49).…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression studies in HEK cells showed that CFTR expression led to a marked increase in Cl Ϫ /OH Ϫ and Cl Ϫ /HCO 3 Ϫ exchange mediated by SLC26A3, -A4, and -A6 (48). It is also possible that, under resting conditions, association between CFTR and pendrin blocks AE activity, a phenomenon recently described for Slc26a9 and the regulatory domain of CFTR in Xenopus oocyte co-expression studies (49).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the STAS domain in SLC26A3 also interacts with cystic fibrosis transmembrane regulator, and this interaction reciprocally modulates cystic fibrosis transmembrane regulator channel function as well as SLC26A3 transporter function (35). In contrast, cystic fibrosis transmembrane regulator interacts with the STAS domain of SLC26A9 and inhibits Cl Ϫ currents as well as its Cl Ϫ -HCO 3 Ϫ exchange (36). Given these data, it was our expectation that MAP1S would modulate NLC.…”
Section: Interaction Between Map1s and Prestin Is Restricted To Specificmentioning
confidence: 93%
“…SLC26A9 (solute carrier family 26, member 9) is a member of the SLC26 family of anion transporters predominantly expressed in epithelia of the lung and upper GI tract (8,9). Recent studies showed that the SLC26A9 protein functions as a Cl -channel with minimal HCO 3 -conductance that is regulated by CFTR and WNK kinases in heterologous cells (10)(11)(12)(13). Further, SLC26A9 contributes to constitutive and cAMP-dependent Cl -secretion in human bronchial epithelial (HBE) cells, where it has been suggested to interact functionally with CFTR in vitro (11,14).…”
Section: Introductionmentioning
confidence: 99%